1980
DOI: 10.1111/j.1151-2916.1980.tb10731.x
|View full text |Cite
|
Sign up to set email alerts
|

J‐Integral Measurements of the Fracture of 50% Alumina Refractories

Abstract: glected. From the present knowledge and understanding of this method, only average velocities for SCG can be determined. The method is particularly suitable for revealing the onset of SCG and in studying the qualitative nature of SCG as a function of strain rate and temperature.The DT method is simple for K,,. evaluation if several test samples are available. The average value of K,, determined for NC-132 Si,N4 at 20°C was =4.1 MN/m3I2. The DT method is especially suitable for determining crack velocities and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
14
0
4

Year Published

1986
1986
2007
2007

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 10 publications
1
14
0
4
Order By: Relevance
“…The two methods require identification of the crack which is propagated. Alternatively, Bradt et al (58) proposed a method for refractory materials with marked non-linear behaviour. The method is based on the difference in areas between the load-displacement curve of an un-notched specimen of the material, where linear elastic behaviour is assumed, and the load-displacement curve of a notched specimen of the same material, which presents nonlinear behaviour (Fig.…”
Section: Determination Of Fracture Parametersmentioning
confidence: 99%
See 3 more Smart Citations
“…The two methods require identification of the crack which is propagated. Alternatively, Bradt et al (58) proposed a method for refractory materials with marked non-linear behaviour. The method is based on the difference in areas between the load-displacement curve of an un-notched specimen of the material, where linear elastic behaviour is assumed, and the load-displacement curve of a notched specimen of the same material, which presents nonlinear behaviour (Fig.…”
Section: Determination Of Fracture Parametersmentioning
confidence: 99%
“…[16]. For materials which present real or apparent ductility, the fracture toughness value, J IC , thus obtained is higher than the critical energy release rate (G IC ) (35,58) and corresponds to that of the component or structure of the same material whose integrity is analyzed if it is in the same deformation state as the beam tested.…”
Section: Determination Of Fracture Parametersmentioning
confidence: 99%
See 2 more Smart Citations
“…The strength measurements thus corroborate the acousto-ultrasonic evaluation that the crack growth in the refractory is quasi-static. Homeny and Bradt [8] studied the single quench thermal shock damage in high alumina castable refractories by measuring flexural strength and observed that the crack growth was quasi-static in all the refractories. AT ("C)…”
mentioning
confidence: 99%